Women’s Empowerment in the Context of Aligarh District - Chauhan, Sheena; Anwer, Tarique (Journal of Neonatal Surgery, 2025)
This Paper entitled “Women’s Empowerment in the Context of Aligarh District” explores the empowerment of women as a general and with special reference to Aligarh District. Even though the term ‘empowerment’ is now accepted in the vocabulary of development, it is hard to define and difficult to implement in this broadest sense. Empowerment may be described as a process that helps people to assert their control over the factors that affect their lives.Since independence, the Government of India has been making various efforts to empower women. In various plan periods, the issues regarding women's empowerment have been given priority. From the fifth five-year plan onwards, there has been a remarkable shift from a welfare-oriented approach of women's empowerment to a development approach. The National Commission for Women was set up by an Act of Parliament in 1990 to safeguard the rights of women. The 73rd and 74th Amendments to the Constitution of India provided an opportunity to women to take part in active politics.Empowerment is not a new idea; it is as old as human civilization. From the beginning of Human Civilization, people have been engaged in the conflict to acquire power. The development of Human Civilization has been going on through the cooperation of both men and women. It is not possible to maintain the creation of a new generation without the help of both genders. So in this aspect, we can say that both men and women are equally important for our continuation of human civilization in the world. Therefore, both men and women must be treated equally. It has been seen that the economic empowerment status of women in our society is very low in practice. The present study tried to find the reason and solution for the upliftment of empowerment of women with reference to Aligarh District.